Cerebral Venous Sinus Thrombosis, Pulmonary Embolism, and Thrombocytopenia After COVID-19 Vaccination in a Taiwanese Man: A Case Report and Literature Review - Lin, Wei; Ko, Chien-An; Sung, Yueh-Feng; Chen, Yeu-Chin; Lee, Jiunn-Tay; Lin, Yun-Qian; Lin, Yu-Kai (Frontiers in Neurology, 2021)
Objective: Coronavirus disease (COVID-19) vaccine-induced immune thrombotic thrombocytopenia (VITT) is a rare but fatal complication observed within 2 weeks of adenovirus-vectored vaccination. Case report: A 52-year-old male patient, with a family history of autoimmune diseases, presented with a new onset of worsening headache with nausea and vomiting, post vaccination. The patient was diagnosed with vaccine-induced immune thrombotic thrombocytopenia based on laboratory findings demonstrating thrombocytopenia, elevated D-dimer, and dural sinus thrombosis identified on neuroimaging. The patient was successfully treated with high-dose immunoglobulin, steroids, and non-heparin anti-coagulant agents, without any neurologic sequelae. Finally, a confirmatory test with anti-platelet factor 4 antibody was strongly positive. Conclusion: Physicians should be vigilant when treating patients presenting with new-onset thunderclap headache, progressive worsening headache, and awakening headache accompanied by nausea or vomiting after vaccination, even though no definite clinical neurological deficits have been identified. Emergency laboratory test results for demonstrating elevated D-dimer levels, decreased platelet count, and neuroimaging correlation are integral for diagnosis and must be the protocol. Treatment with non-heparin anticoagulants, high-dose intravenous immunoglobulin, and steroids that halt or slow down the immune-mediated prothrombotic process should be initiated immediately. Considering the high mortality rate of VITT, treatment should be initiated prior to confirmatory test results.